Resting State Functional Connectivity of Dorsal Raphe Nucleus and Ventral Tegmental Area in Medication-Free Young Adults With Major Depression - Anand, Amit; Jones, Stephen E.; Lowe, Mark; Karne, Harish; Koirala, Parashar (Frontiers in Psychiatry, 2019)
Background: This study for the first time investigated dorsal raphe nucleus (DRN) and ventral tegmental area (VTA) resting state whole-brain functional connectivity in medication-free young adults with major depression (MDD) at baseline and in relationship to treatment response. Method: A total of 119 subjects: 78 MDD (24+4 yrs.) and 41 Healthy Controls (HC) (24+3 yrs.) were included in the analysis. DRN and VTA ROIs anatomical templates were used to extract resting state fluctuations and used to derive whole-brain functional connectivity. Differences between MDD and HCs were examined as well as correlation of baseline Hamilton Depression and Anxiety scale scores to baseline DRN and VTA connectivity. Relationship to treatment response was examined by investigating correlation of percent decrease in depression and anxiety scale scores with baseline connectivity measures. Results: There was a significant decrease (p=0.05; cluster-wise corrected) in DRN connectivity with the prefrontal and mid-cingulate cortex in MDD group compared to HC group. DRN connectivity with temporal areas including the hippocampus and amygdala positively correlated with baseline depression scores (p=0.05;cluster-wise corrected). VTA connectivity with the cuneus-occipital areas correlated with change in depression scores (p=0.05; cluster-wise corrected). Conclusion: Our results indicate DRN-prefrontal and DRN-cingulate cortex connectivity abnormalities in young medication-free depressed subjects compared to HCs and that severity of depressive symptoms correlates with DRN-amygdala/hippocampus connectivity. VTA connectivity with the parietal and occipital areas is related to antidepressant treatment associated decrease in depressive symptoms. Future studies need to be done in larger and different age group populations to confirm the findings of the study.